2002
DOI: 10.1080/135475001100744192
|View full text |Cite
|
Sign up to set email alerts
|

Urinary homovanillic acid and serum prolactin levels in children with low environmental exposure to lead

Abstract: Current evidence suggests that the neurotoxic effects of lead may partially be mediated through interference with the dopaminergic system. The aim of this study was to assess the levels of two peripheral dopaminergic markers--serum prolactin (Pro-S) and urinary homovanillic acid (HVA-U)--in children living around two lead smelters, who are presumed to be exposed to high environmental lead pollution (n = 200), and compare their results with 200 age- and sex-matched controls living in an area unpolluted by heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This finding is in agreement with some previous studies reporting that boys tend to have a higher uptake of environmental heavy metals than girls, principally due to behavioral differences [68]. Another factor that can explain this difference related to gender is shown in Table 4; as the BCLs in children increase with the increasing number of cigarettes smoked at home.…”
Section: Total Blood Mercurysupporting
confidence: 82%
“…This finding is in agreement with some previous studies reporting that boys tend to have a higher uptake of environmental heavy metals than girls, principally due to behavioral differences [68]. Another factor that can explain this difference related to gender is shown in Table 4; as the BCLs in children increase with the increasing number of cigarettes smoked at home.…”
Section: Total Blood Mercurysupporting
confidence: 82%
“…Analogical results were obtained in a group of 101 pregnant women, 13 while no significant association between prolactin and lead levels was found in 400 children environmentally exposed to lead. 10 However, Govoni et al 14 showed higher level of prolactin in a group of male workers occupationally exposed to lead with blood lead levels higher than 40 µd/dl than in those with blood lead level below this value. Similarly, Lucchini et al 15 found higher prolactin level in a group of 66 lead-exposed workers with mean blood lead level 27.50 ± 28 µg/dl than in an unexposed control group with mean blood lead level of 8.11 ± 4.47 µg/dl.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a biphasic dose-dependent effect of lead on the dopaminergic neurotransmission has been postulated as well. 10 An existence of such mechanism may explain also discordant results of studies on prolactinemia in lead exposure. In the present study, prolactin level was significantly lower in workers chronically exposed to lead than in the control group, while a short-term exposure to lead did not significantly affect its level.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of organic acids in urine have been measured for diagnosis of inborn errors of metabolism and as markers of essential nutrient status, neurotransmitter disturbances, toxicant effects and small intestinal microbial overgrowth. [1][2][3][4][5][6][7][8] Elevations of specific organic acids have been reported as markers of nutritional deficiencies, including xanthurenic acid (vitamin B 6 ), 9 formiminoglutamic acid (folic acid), 10 and 3-hydroxyisovaleric acid (biotin). 11 Neurotransmitter metabolites in urine have been found useful in studies of cancer 12 and behavioral disorders, 13 and exposure to xenobiotic compounds has been monitored by measuring excreted metabolic products.…”
Section: Introductionmentioning
confidence: 99%
“…14 Rationales for using organic acids as markers of various disorders have been reviewed. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Variability of urinary analytes has been the subject of multiple reports. [16][17][18][19] When 10 overnight urine samples were collected by 10 patients with non-insulin-dependent diabetes mellitus, urinary albumin excretion showed total variability of 12%.…”
Section: Introductionmentioning
confidence: 99%